Material for perovskite solar cell, perovskite solar cell, and electric device

By using perovskite solar cell materials with specific compound structures in perovskite solar cells, the problem of inefficient energy conversion efficiency of perovskite solar cells is solved, and higher carrier transmission performance and structural stability are achieved.

CN119855466APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311349445.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

How to further improve the energy conversion efficiency of perovskite solar cells and solve the problem of inefficiency in the production process.

Method used

A perovskite solar cell material is used, which includes a specific compound structure. It combines thiophene, alkoxy groups and conjugated groups through a pyridine ring as the core framework to improve the solubility and micromorphology of the compound, and adjust the energy level structure to improve the carrier transport performance.

Benefits of technology

By improving the carrier transmission performance of perovskite solar cell materials, enhancing the structural stability and interface quality of the material, the energy conversion efficiency of perovskite solar cells is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855466A_ABST
    Figure CN119855466A_ABST
Patent Text Reader

Abstract

The invention provides a material for a perovskite solar cell, the perovskite solar cell and a power utilization device, the material for the perovskite solar cell comprises the material for the perovskite solar cell and at least one of a compound shown in a formula (Z) and a compound shown in a formula (X), in the formula (Z), in the formula (Z), in the formula (X), in the formula (X), in the formula (X), in the formula (X), in the formula (X), in the formula (X); each of R11 and R12 independently comprises an alkyl-substituted thiophene group or an alkyl-substituted aryl group, and the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group; y11 and Y12 each independently comprise a conjugated group; in the formula (X), R21 and R22 each independently comprise an alkyl-substituted thiophene group and an alkyl-substituted aryl group, and the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group; y21 and Y22 each independently include a conjugated group. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of solar cells, and in particular relates to a material for a perovskite solar cell, a perovskite solar cell and an electrical device. Background Art

[0002] Perovskite solar cells are solar cells that use organic metal halide perovskite materials as light-absorbing layers. They have excellent photoelectric properties and simple preparation methods, bringing new space and hope for photovoltaic power generation.

[0003] In the production process of perovskite solar cells, how to further improve their energy conversion efficiency is an urgent problem to be solved. Summary of the invention

[0004] The present application provides a material for a perovskite solar cell, a perovskite solar cell and an electrical device, which can improve the energy conversion efficiency of the perovskite solar cell.

[0005] The embodiment of the first aspect of the present application provides a material for a perovskite solar cell, comprising at least one of a compound represented by formula (Z) and a compound represented by formula (X),

[0006]

[0007] In formula (Z),

[0008] R 11 and R 12 Each independently includes an alkyl-substituted thiophene group or an alkyl-substituted aryl group, wherein the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group;

[0009] Y 11 and Y 12 Each independently includes a conjugated group;

[0010] In formula (X),

[0011] R 21 and R 22 Each independently includes an alkyl-substituted thiophene group, an alkyl-substituted aryl group, wherein the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group;

[0012] Y 21 and Y 22 Each independently includes a conjugated group

[0013] Thus, the compound according to the embodiment of the present application has a pyridine ring as the core skeleton structure, coordinated with thiophene, alkoxy, Y 11 , Y 12 , Y 11 and Y 12Groups such as these can improve the solubility of the compound and adjust the microscopic morphology of the film after formation; they can also adjust the energy level structure and enhance the carrier transport performance, thereby improving the energy conversion efficiency.

[0014] In some embodiments, Y 11 and Y 12 Each independently includes an aryl derivative; optionally, Y 11 and Y 12 Each independently comprises the structural formula represented by formula (A),

[0015]

[0016] In formula (A),

[0017] M1 and M2 each independently include

[0018] At least one of;

[0019] M3 includes at least one of a hydrogen atom and a halogen atom; optionally, M3 includes a hydrogen atom or a halogen atom.

[0020] Y 11 and Y 12 When the above groups are included independently, the compound also includes active groups such as carbonyl groups, which can enhance the interaction between the defects of the perovskite material and the free ions, further passivate the defect state energy levels of the perovskite material, and improve the structural stability of the perovskite material, thereby improving the energy conversion efficiency.

[0021] In some embodiments, Y 11 and Y 12 Each independently comprises at least one of the structural formulas represented by formula (A-1) to formula (A-9),

[0022]

[0023]

[0024] In some embodiments, R 11 and R 12 Each independently includes an alkyl-substituted thiophene group, wherein the alkyl-substituted thiophene group includes the structural formula shown in formula (C),

[0025]

[0026] R 13 including substituted or unsubstituted C6 to C16 straight chain alkyl groups;

[0027] Further optionally, R 11 and R 12The same groups are included.

[0028] Adjustment of the chain length of the above groups can adjust their solubility parameters in halogenated solvents. For example, within the optional range, the solubility parameter is higher and the solubility performance is improved.

[0029] In some embodiments, the perovskite solar cell material includes at least one of the compounds represented by formula (Z-11) to the compounds represented by formula (Z-18),

[0030]

[0031]

[0032]

[0033]

[0034]

[0035] In some embodiments, R 11 and R 12 Each independently includes an alkyl-substituted aryl group, wherein the alkyl-substituted aryl group includes the structural formula shown in formula (D),

[0036]

[0037] R 14 including substituted or unsubstituted C6 to C16 straight chain alkyl groups;

[0038] Optionally, the alkyl-substituted aryl group includes the structural formula shown in formula (D-1),

[0039]

[0040] Further optionally, R 11 and R 12 The same groups are included.

[0041] Adjustment of the chain length of the above groups can adjust their solubility parameters in halogenated solvents. For example, within the optional range, the solubility parameter is higher and the solubility performance is improved.

[0042] In some embodiments, the perovskite solar cell material includes at least one of the compounds represented by formula (Z-21) to the compounds represented by formula (Z-28),

[0043]

[0044]

[0045]

[0046]

[0047] In some embodiments, Y 21 and Y 22 Each independently includes an aryl derivative; optionally, Y 21 and Y 22 Each independently comprises the structural formula represented by formula (B),

[0048]

[0049] In formula (B),

[0050] Q1 and Q2 each independently include

[0051] At least one of;

[0052] Q3 includes at least one of a hydrogen atom and a halogen atom; optionally, Q3 includes a hydrogen atom or a halogen atom.

[0053] Y 21 and Y 22 When the above groups are included independently, the compound also includes active groups such as carbonyl groups, which can enhance the interaction between the defects of the perovskite material and the free ions, further passivate the defect state energy levels of the perovskite material, and improve the structural stability of the perovskite material, thereby improving the energy conversion efficiency.

[0054] Further optionally, Y 21 and Y 22 Each independently comprises at least one of the structural formulas represented by formula (B-1) to formula (B-9),

[0055]

[0056] In some embodiments, R 21 and R 22 Each independently includes an alkyl-substituted thiophene group, wherein the alkyl-substituted thiophene group includes the structural formula shown in formula (E),

[0057]

[0058] R 23 including substituted or unsubstituted C6 to C16 straight chain alkyl groups;

[0059] Further optionally, R 21 and R 22The adjustment of the chain length of the above groups can adjust the solubility parameter in the halogenated solvent, for example, the solubility parameter is higher within the optional range, and the solubility performance is improved.

[0060] In some embodiments, the perovskite solar cell material includes at least one of the compounds represented by formula (X-11) to the compounds represented by formula (X-17),

[0061]

[0062]

[0063]

[0064]

[0065] In some embodiments, R 21 and R 22 Each independently includes an alkyl-substituted aryl group, wherein the alkyl-substituted aryl group includes the structural formula shown in formula (F),

[0066]

[0067] R 24 including substituted or unsubstituted C6 to C16 straight chain alkyl groups;

[0068] Optionally, the alkyl-substituted aryl group includes the structural formula shown in formula (F-1),

[0069]

[0070] Further optionally, R 21 and R 22 The adjustment of the chain length of the above groups can adjust the solubility parameter in the halogenated solvent, for example, the solubility parameter is higher within the optional range, and the solubility performance is improved.

[0071] In some embodiments, the perovskite solar cell material includes at least one of the compounds represented by formula (X-21) to the compounds represented by formula (X-28),

[0072]

[0073]

[0074]

[0075]

[0076] In a second aspect, an embodiment of the present application proposes a perovskite solar cell, comprising a perovskite absorption layer, a hole transport layer and an electron transport layer, the perovskite absorption layer comprising two sides opposite to each other along its thickness direction; the hole transport layer is arranged on one side of the perovskite absorption layer; the electron transport layer is arranged on the side of the perovskite absorption layer away from the hole transport layer, and the electron transport layer comprises the material for a perovskite solar cell as described in any embodiment of the first aspect of the present application.

[0077] In a third aspect, an embodiment of the present application proposes a perovskite solar cell, comprising a perovskite absorption layer, a hole transport layer, an electron transport layer and a passivation layer, wherein the perovskite absorption layer comprises two sides opposite to each other along its thickness direction; the hole transport layer is arranged on one side of the perovskite absorption layer; the electron transport layer is arranged on the side of the perovskite absorption layer away from the hole transport layer, and the passivation layer is arranged between the perovskite absorption layer and the electron transport layer, and the passivation layer comprises the material for a perovskite solar cell as described in any embodiment of the first aspect of the present application.

[0078] In a fourth aspect, an embodiment of the present application proposes an electrical device, comprising the perovskite solar cell described in any embodiment of the second aspect or any embodiment of the third aspect of the present application.

[0079] In a fifth aspect, an embodiment of the present application proposes a photovoltaic module, including a perovskite solar cell according to any embodiment of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0081] Figure 1 A schematic diagram of the structure of a perovskite solar cell provided in some embodiments of the present application;

[0082] Figure 2 is a schematic diagram of the structure of a perovskite solar cell provided in some other embodiments of the present application;

[0083] Figure 3 It is a schematic diagram of the structure of an electrical device provided in some embodiments of the present application.

[0084] In the drawings, the drawings are not necessarily drawn to scale.

[0085] Among them, the reference numerals in the figure are:

[0086] X, thickness direction;

[0087] 10. Perovskite absorption layer;

[0088] 20. Hole transport layer;

[0089] 30. Electron transport layer;

[0090] 40. Passivation layer. DETAILED DESCRIPTION

[0091] Hereinafter, the embodiments of the materials for perovskite solar cells, perovskite solar cells, photovoltaic modules and electrical devices of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0092] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0093] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0094] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0095] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0096] The term "alkyl" encompasses straight and branched alkyl groups. For example, the alkyl group may be a C5-C500 alkyl group, a C20-C400 alkyl group, a C1-C50 alkyl group, a C1-C40 alkyl group, a C1-C30 alkyl group, a C1-C20 alkyl group, a C1-C12 alkyl group, a C1-C10 alkyl group, a C1-C6 alkyl group, a C1-C4 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a cyclobutyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, a heptyl group, a cycloheptyl group, an octyl group, a cyclooctyl group, a nonyl group, and a decyl group. In addition, the alkyl group may be optionally substituted. The term "haloalkyl" refers to an alkyl group in which a hydrogen atom is partially or completely replaced by a halogen atom, and the term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and the like.

[0097] The term "alkoxy" encompasses straight and branched alkoxy groups. For example, alkoxy groups can be C5-C500 alkoxy groups, C20-C400 alkoxy groups, C1-C50 alkoxy groups, C1-C40 alkoxy groups, C1-C30 alkoxy groups, C1-C20 alkoxy groups, C1-C12 alkoxy groups, C1-C10 alkoxy groups, C1-C6 alkoxy groups, C1-C4 alkoxy groups. In some embodiments, alkoxy groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, the tert-butyl, cyclobutyl, pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, hexyl, cyclohexyl, heptyl, cycloheptyl, octyl, cyclooctyl, nonyl and decyl etc. In addition, alkoxy groups can be optionally substituted. The term "haloalkoxy" refers to an alkoxy group in which hydrogen atoms are partially or completely replaced by halogen atoms, and the term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom, an iodine atom and the like.

[0098] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D) or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).

[0099] At various places in the present specification, substituents of compounds are disclosed in groups or in ranges. It is expressly intended that such description includes every individual subcombination of the members of these groups and ranges. For example, the term "C1-C8 alkoxy" is specifically intended to disclose individually C1, C2, C3, C4, C5, C6, C7, C8, C1-C8, C1-C7, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C8, C2-C7, C2-C6, C2-C5, C2-C4, C2-C3, C3-C8, C3-C7, C3-C6, C3-C5, C3-C4, C4-C8, C4-C7, C4-C6, C4-C5, C5-C8, C5-C7, C5-C6, C6-C8, C6-C7, and C7-C8 alkoxy.

[0100] As other examples, the integers in the range of 5-40 are specifically intended to disclose individually 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40; the integers in the range of 1-20 are specifically intended to disclose individually 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. Accordingly, other groups or ranges are specifically contemplated.

[0101] When the above groups are substituted, the substituents may be independently selected from halogen atoms or heteroatoms.

[0102] Perovskite solar cells include a perovskite absorption layer, a hole transport layer, an electron transport layer, and electrodes. The working process of a perovskite cell mainly includes: the generation and separation of excitons, the transport of free carriers, the collection of carriers, and the generation of current. The specific process is as follows: In a perovskite solar cell, sunlight is absorbed by the perovskite absorption layer, and the perovskite absorption layer absorbs photons to generate excitons. Since the perovskite absorption layer has a lower Coulomb force binding, the excitons are then separated into free electrons and holes. The separated free carriers are transmitted in the perovskite absorption layer and transmitted out through the transport layer. The electron transport layer plays the role of transmitting electrons and blocking holes, and the hole transport layer plays the role of transmitting holes and blocking electrons. The electrons and holes transmitted through the transport layer are collected by the electrodes to form current.

[0103] The material properties of perovskite solar cells make it easy for ions to migrate to the electrodes under light and / or heat conditions, causing the crystal lattice of the metal electrode to be destroyed, and metals with a certain strength to form brittle metal oxides. It is also easy for charges to accumulate at the interface, causing the flat band potential to decrease, and carrier transport to be further hindered, affecting the energy conversion efficiency of perovskite solar cells.

[0104] In view of the above problems, the present application proposes a material for perovskite solar cells, which has a dense film layer after the perovskite solar cell material forms a film layer, which can reduce the number of ions migrating to the electrode, improve the device structure stability of the perovskite solar cell, and improve the energy conversion efficiency of the perovskite solar cell; and the film layer also has a certain hydrophobicity, which can play a certain barrier role to external water and oxygen while blocking the migration of ions, reduce the risk of water and oxygen eroding the perovskite absorption layer and causing perovskite degradation, further improve the device structure stability, and further improve the energy conversion efficiency of the perovskite solar cell. Next, the perovskite solar cell material of the present application is described in detail.

[0105] Materials for perovskite solar cells

[0106] In a first aspect, the present application provides a material for a perovskite solar cell, wherein the material for a perovskite solar cell comprises at least one of a compound represented by formula (Z) and a compound represented by formula (X),

[0107]

[0108] In formula (Z),

[0109] R 11 and R 12 Each independently includes an alkyl-substituted thiophene group or an alkyl-substituted aryl group, wherein the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group;

[0110] Y 11 and Y 12 each independently comprises a conjugated group;

[0111]

[0112] In formula (X),

[0113] R 21 and R 22 Each independently includes an alkyl-substituted thiophene group, an alkyl-substituted aryl group, wherein the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group;

[0114] Y 21 and Y 22 Each independently includes a conjugated group.

[0115] In some embodiments, the material for a perovskite solar cell includes a compound represented by formula (Z).

[0116] In some embodiments, the material for a perovskite solar cell includes a compound represented by formula (X).

[0117] In some embodiments, the material for a perovskite solar cell includes a compound represented by formula (Z) and a compound represented by formula (X).

[0118] [Compound represented by formula (Z)]

[0119] The compound represented by formula (Z) is a condensed ring electron acceptor unit with a double "T" structure. The double "T" structure is due to the same R 11 With R 12 The connected C atoms produce a SP-like 2 The hybrid orbital forms an angle of ~120°, so that the basic skeleton structure of the overall compound presents a chemical structure with a lower "T" and an upper "T", so it is defined as a double "T" structure in the implementation manner of the present application.

[0120] The core skeleton structure has a pyrazine ring, which includes a N atom with a lone pair of electrons, and the lone pair of electrons on the N atom and two σ bonds are SP 2 The lone pair of electrons on the N atom is formed by a hybrid orbital, so it is difficult for the lone pair of electrons on the p orbital to participate in the conjugated system. Therefore, the lone pair of electrons on the N atom is still nucleophilic and can react with cations in the perovskite absorption layer, such as Pb 2+ and MA + The cations generate coordination bond-like forces, which can effectively isolate the migration of cations and passivate the defects caused by cation occupancy. The basic skeleton is a large conjugated structure. The S atom in thiophene is SP 3 Hybrid orbitals, in which two pairs of lone pairs of electrons occupy two orbitals respectively and are not perpendicular to the conjugated π bonds, can form p-π conjugation with the conjugated π bond system, making the overall basic skeleton structure electron-rich. 11 and Y 12 The polar groups on the group, as electron-withdrawing groups, can shift the electron cloud of the basic skeleton structure to both ends, forming a chemical structure of A (electron-deficient)-D (electron-donating)-A (electron-deficient), which has intramolecular charge transfer (ICT) characteristics and can facilitate directional carrier transport. 11 and Y 12 It can also form a certain dipole moment within the molecule, enhance the intermolecular force, and form a dense film. 11 and Y 12Polar groups such as carbonyl groups on the perovskite can passivate the surface defects of the perovskite, thereby improving the interface quality between the perovskite and the electron transport layer, thereby improving the overall device efficiency and stability. The conjugated structure itself can also participate in the large conjugated π bond, laterally extend the conjugation length, improve the carrier transport performance, and improve the energy conversion efficiency. And the energy level of the entire compound can also be adjusted by regulating its strong electron-withdrawing groups.

[0121] R 11 and R 12 including an alkyl-substituted thiophene group or an alkyl-substituted aryl group, R 11 and R 12 It has π-π conjugation and can participate in the large conjugated π bond of the basic skeleton structure, further widening the conjugated plane in the direction perpendicular to the main chain, which is beneficial to the improvement of the carrier transmission performance in the three-dimensional direction (3D). 11 and R 12 It also has an important function relative to the compound: improving the solubility of the overall compound. 11 and R 12 The alkyl molecules in the compound have strong intermolecular forces with the organic solvent molecules (mainly dispersion / induction forces), resulting in a solvation effect and good solubility in organic solvents. Therefore, adding an alkyl chemical structure can improve the solubility of the compound in organic solvents.

[0122] Compounds with large conjugated structures have a strong π-π stacking effect. The interaction between the same molecules is much greater than the interaction between the same solvent molecules. Therefore, their solubility in solvents is relatively poor and they are difficult to dissolve in common organic solvents (such as toluene, chlorobenzene, chloroform, dichloromethane, DMF, DMSO, etc.). Therefore, the introduction of R 11 and R 12It can improve its solubility in organic solvents and achieve the purpose of solubilization in solvents. The longer the alkyl chain, the more obvious the improvement of its solubility (alkyl molecules and organic solvent molecules have strong intermolecular forces such as dispersion and / or induction), resulting in a solvation effect, and having good solubility in organic solvents. Therefore, the chemical structure of adding alkyl can increase the solubility of the compound in organic solvents. The longer the alkyl chain, the more it can increase the interaction between the same solvent molecules, which can further improve the solubility of the overall compound. In addition, such compounds as electron transport layers or passivation layers need to maintain the planarity of the overall molecular structure and the effect of π-π stacking (π-π stacking can induce molecules to arrange and crystallize regularly, forming a relatively dense film layer, and blocking the migration of insulators in a physical barrier manner; the compound has good planarity, produces a large conjugated plane, and can improve the electron transport performance) to ensure that it can have good performance of blocking insulators and electron transport. However, longer alkyl and branched alkyl groups will produce greater steric effects in the molecular structure, destroying the molecular planarity and the effect of π-π stacking, so longer straight alkyl and branched alkyl groups will have an adverse effect on the carrier transport performance. Therefore, in the embodiment of the present application, the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group, which can take into account the improvement of the solubility and carrier transport performance of the compound.

[0123] Since the compound itself has a large conjugated structure, the interaction force between its own molecules is much greater than the interaction force with water. Therefore, it is difficult to dissolve in water and has good hydrophobic properties. It can play a certain barrier role against external water and oxygen while preventing the migration of isolators, reducing the risk of water and oxygen corroding the perovskite absorption layer and causing perovskite degradation, further improving the device structure stability, and further improving the energy conversion efficiency of perovskite solar cells.

[0124] Thus, the compound according to the embodiment of the present application has a pyrazine ring as the core skeleton structure, coordinated with thiophene, alkyl, Y 11 and Y 12 Groups such as these can improve the solubility of the compound and adjust the microscopic morphology of the film after formation; they can also adjust the energy level structure and enhance the carrier transport performance, thereby improving the energy conversion efficiency.

[0125] In some embodiments, Y 11 and Y 12 Each independently includes an aryl derivative; optionally, Y 11 and Y 12 Each independently comprises the structural formula represented by formula (A),

[0126]

[0127] In formula (A),

[0128] M1 and M2 each independently include

[0129] At least one of;

[0130] M3 includes at least one of a hydrogen atom and a halogen atom; optionally, M3 includes a hydrogen atom or a halogen atom. M3 can replace two hydrogen atoms in an aryl group, and the two hydrogen atoms can be hydrogen atoms connected to adjacent carbon atoms in the aryl group. The halogen atom can include at least one of a fluorine atom and a chlorine atom.

[0131] Y 11 and Y 12 The ortho position of the C atom to which the group is connected to the skeleton structure has a strong electron-withdrawing group (such as a carbonyl group), so that the overall structure constitutes an electron-withdrawing group. Optionally, further introducing at least one of the fluorine atoms and chlorine atoms contained in M3 can further increase the overall molecular polarity.

[0132] In some embodiments, Y 11 and Y 12 Each independently comprises at least one of the structural formulas represented by formula (A-1) to formula (A-9),

[0133]

[0134] Y 11 and Y 12 When the above groups are included independently, the compound also includes polar groups such as carbonyl groups, which can enhance the interaction between the defects of the perovskite material and the free ions, further passivate the defect state energy levels of the perovskite material, and improve the structural stability of the perovskite material, thereby improving the energy conversion efficiency.

[0135] Taking into account the steric effect and the energy level matching of the perovskite absorption layer, further optionally, Y 11 and Y 12 Each independently comprises at least one of the following structural formulas,

[0136]

[0137]

[0138] In some embodiments, R 11 and R 12 Each independently includes an alkyl-substituted thiophene group, wherein the alkyl-substituted thiophene group includes the structural formula shown in formula (C),

[0139]

[0140] R 13It can be a branched alkyl group or a straight-chain alkyl group, and can be a straight-chain alkyl group. The steric hindrance of the straight-chain alkyl group is relatively smaller, which is more conducive to the compound forming a dense film layer. 13 A substituted or unsubstituted C5 to C20 straight chain alkyl group may be included.

[0141] Optionally, R 13 The group includes substituted or unsubstituted C6 to C16 straight chain alkyl groups. The adjustment of the chain length of the above group can adjust its solubility parameter in the halogenated solvent, for example, within the optional range, the solubility parameter is higher and the solubility performance is improved.

[0142] For example, R 13 Including substituted or unsubstituted C5 straight chain alkyl, C6 straight chain alkyl, C7 straight chain alkyl, C8 straight chain alkyl, C9 straight chain alkyl, C10 straight chain alkyl, C11 straight chain alkyl, C12 straight chain alkyl, C13 straight chain alkyl, C14 straight chain alkyl, C15 straight chain alkyl, C16 straight chain alkyl, C17 straight chain alkyl, C18 straight chain alkyl, C19 straight chain alkyl, C20 straight chain alkyl or a range consisting of any two of the above values.

[0143] In some embodiments, R 11 and R 12 The same groups can be included to simplify the reaction process. 11 and R 12 They may also be different groups.

[0144] Exemplarily, the perovskite solar cell material includes at least one of the compounds represented by formula (Z-11) to the compounds represented by formula (Z-18),

[0145]

[0146]

[0147]

[0148]

[0149] In some embodiments, R 11 and R 12 Each independently includes an alkyl-substituted aryl group, wherein the alkyl-substituted aryl group includes the structural formula shown in formula (D),

[0150]

[0151] R 14 It can be a branched alkyl group or a straight-chain alkyl group, and can be a straight-chain alkyl group. The steric hindrance of the straight-chain alkyl group is relatively smaller, which is more conducive to the compound forming a dense film layer.14 A substituted or unsubstituted C5 to C20 straight chain alkyl group may be included.

[0152] R 14 Including substituted or unsubstituted C6 to C20 straight-chain alkyl groups; the adjustment of the chain length of the above group can adjust its solubility parameter in the halogenated solvent, for example, the solubility parameter is higher within the optional range and the solubility performance is improved.

[0153] For example, R 14 Including substituted or unsubstituted C5 straight chain alkyl, C6 straight chain alkyl, C7 straight chain alkyl, C8 straight chain alkyl, C9 straight chain alkyl, C10 straight chain alkyl, C11 straight chain alkyl, C12 straight chain alkyl, C13 straight chain alkyl, C14 straight chain alkyl, C15 straight chain alkyl, C16 straight chain alkyl, C17 straight chain alkyl, C18 straight chain alkyl, C19 straight chain alkyl, C20 straight chain alkyl or a range consisting of any two of the above values.

[0154] R 14 It can be grafted at the para, ortho or meta position in the benzene ring. Optionally, the alkyl-substituted aryl group includes the structural formula shown in formula (D-1),

[0155]

[0156] The alkyl group at the para position has less steric hindrance than the ortho / meta positions and has the least effect on the planarity of the overall compound.

[0157] In some embodiments, R 11 and R 12 Including the same group is beneficial to simplify the reaction process. 11 and R 12 They may also be different groups.

[0158] Exemplarily, the perovskite solar cell material includes at least one of the compounds represented by formula (Z-21) to the compounds represented by formula (Z-28),

[0159]

[0160]

[0161]

[0162]

[0163]

[0164] [Compound represented by formula (X)]

[0165] The compound represented by formula (X) is a condensed ring electron acceptor unit having a double "T" structure. The double "T" structure is due to the same R 21 With R 22 The connected C atoms produce a SP-like 2 The hybrid orbital forms an angle of ~120°, so that the basic skeleton structure of the overall compound presents a chemical structure with a lower "T" and an upper "T", so it is defined as a double "T" structure in the implementation manner of the present application.

[0166] The core skeleton structure has a pyrazine ring, which includes a N atom with a lone pair of electrons, and the lone pair of electrons on the N atom and two σ bonds are SP 2 The lone pair of electrons on the N atom is formed by a hybrid orbital, so it is difficult for the lone pair of electrons on the p orbital to participate in the conjugated system. Therefore, the lone pair of electrons on the N atom is still nucleophilic and can react with cations in the perovskite absorption layer, such as Pb 2+ and MA + The cations generate coordination bond-like forces, which can effectively isolate the migration of cations and passivate the defects caused by cation occupancy. The basic skeleton is a large conjugated structure. The S atom in thiophene is SP 3 Hybrid orbitals, in which two pairs of lone pairs of electrons occupy two orbitals respectively and are not perpendicular to the conjugated π bonds, can form p-π conjugation with the conjugated π bond system, making the overall basic skeleton structure electron-rich. 21 and Y 22 The polar groups on the group, as electron-withdrawing groups, can shift the electron cloud of the basic skeleton structure to both ends, forming a chemical structure of A (electron-deficient)-D (electron-donating)-A (electron-deficient), which has intramolecular charge transfer (ICT) characteristics and can facilitate directional carrier transport. 11 and Y 12 It can also form a certain dipole moment within the molecule, enhance the intermolecular force, and form a dense film. 11 and Y 12 Polar groups such as carbonyl groups on the perovskite can passivate the surface defects of the perovskite, thereby improving the interface quality between the perovskite and the electron transport layer, thereby improving the overall device efficiency and stability. The conjugated structure itself can also participate in the large conjugated π bond, laterally extend the conjugation length, improve the carrier transport performance, and improve the energy conversion efficiency. And the energy level of the entire compound can also be adjusted by regulating its strong electron-withdrawing groups.

[0167] R 21 and R 22 including an alkyl-substituted thiophene group or an alkyl-substituted aryl group, R 21 and R 22It has π-π conjugation and can participate in the large conjugated π bond of the basic skeleton structure, further widening the conjugated plane in the direction perpendicular to the main chain, which is beneficial to the improvement of the carrier transmission performance in the three-dimensional direction (3D). 21 and R 22 It also has an important function relative to the compound: improving the solubility of the overall compound. 21 and R 22 The alkyl molecules in the compound have strong intermolecular forces with the organic solvent molecules (mainly dispersion / induction forces), resulting in a solvation effect and good solubility in organic solvents. Therefore, adding an alkyl chemical structure can improve the solubility of the compound in organic solvents.

[0168] Compounds with large conjugated structures have a strong π-π stacking effect. The interaction between the same molecules is much greater than the interaction between the same solvent molecules. Therefore, their solubility in solvents is relatively poor and they are difficult to dissolve in common organic solvents (such as toluene, chlorobenzene, chloroform, dichloromethane, DMF, DMSO, etc.). Therefore, the introduction of R 11 and R 12 It can improve its solubility in organic solvents and achieve the purpose of solubilization in solvents. The longer the alkyl chain, the more obvious the improvement of its solubility (alkyl molecules and organic solvent molecules have strong intermolecular forces such as dispersion and / or induction), resulting in a solvation effect, and having good solubility in organic solvents. Therefore, the chemical structure of adding alkyl can increase the solubility of the compound in organic solvents. The longer the alkyl chain, the more it can increase the interaction between the same solvent molecules, which can further improve the solubility of the overall compound. In addition, such compounds as electron transport layers or passivation layers need to maintain the planarity of the overall molecular structure and the effect of π-π stacking (π-π stacking can induce molecules to arrange and crystallize regularly, forming a relatively dense film layer, and blocking the migration of insulators in a physical barrier manner; the compound has good planarity, produces a large conjugated plane, and can improve the electron transport performance) to ensure that it can have good performance of blocking insulators and electron transport. However, longer alkyl and branched alkyl groups will produce greater steric effects in the molecular structure, destroying the molecular planarity and the effect of π-π stacking, so longer straight alkyl and branched alkyl groups will have an adverse effect on the carrier transport performance. Therefore, in the embodiment of the present application, the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group, which can take into account the improvement of the solubility and carrier transport performance of the compound.

[0169] Since the compound itself has a large conjugated structure, the interaction force between its own molecules is much greater than the interaction force with water. Therefore, it is difficult to dissolve in water and has good hydrophobic properties. It can play a certain barrier role against external water and oxygen while preventing the migration of isolators, reducing the risk of water and oxygen corroding the perovskite absorption layer and causing perovskite degradation, further improving the device structure stability, and further improving the energy conversion efficiency of perovskite solar cells.

[0170] Thus, the compound according to the embodiment of the present application has a pyrazine ring as the core skeleton structure, coordinated with thiophene, alkyl, Y 21 and Y 22 Groups such as these can improve the solubility of the compound and adjust the microscopic morphology of the film after formation; they can also adjust the energy level structure and enhance the carrier transport performance, thereby improving the energy conversion efficiency.

[0171] In some embodiments, Y 21 and Y 22 Each independently includes an aryl derivative; optionally, Y 21 and Y 22 Each independently comprises the structural formula represented by formula (B),

[0172]

[0173] In formula (B),

[0174] Q1 and Q2 each independently include

[0175] At least one of;

[0176] Q3 includes at least one of a hydrogen atom and a halogen atom; optionally, Q3 includes a hydrogen atom or a halogen atom.

[0177] Y 21 and Y 22 The ortho position of the C atom to which the group is connected to the skeleton structure has a strong electron-withdrawing group (such as a carbonyl group), so that the overall structure constitutes an electron-withdrawing group. Optionally, further introducing at least one of the fluorine atom and the chlorine atom contained in Q3 can further increase the overall molecular polarity.

[0178] In some embodiments, Y 21 and Y 22 Each independently comprises at least one of the structural formulas represented by formula (B-1) to formula (B-9),

[0179]

[0180] Y 21 and Y 22When the above groups are included independently, the compound also includes active groups such as carbonyl groups, which can enhance the interaction between the defects of the perovskite material and the free ions, further passivate the defect state energy levels of the perovskite material, and improve the structural stability of the perovskite material, thereby improving the energy conversion efficiency.

[0181] Taking into account the steric effect and the energy level matching of the perovskite absorption layer, further optionally, Y 21 and Y 22 Each independently comprises at least one of the following structural formulas,

[0182]

[0183]

[0184] In some embodiments, R 21 and R 22 Each independently includes an alkyl-substituted thiophene group, wherein the alkyl-substituted thiophene group includes the structural formula shown in formula (E),

[0185]

[0186] R 23 It can be a branched alkyl group or a straight-chain alkyl group, and can be a straight-chain alkyl group. The steric hindrance of the straight-chain alkyl group is relatively smaller, which is more conducive to the compound forming a dense film layer. 23 A substituted or unsubstituted C5 to C20 straight chain alkyl group may be included.

[0187] Optionally, R 23 The group includes substituted or unsubstituted C6 to C16 straight chain alkyl groups. The adjustment of the chain length of the above group can adjust its solubility parameter in the halogenated solvent, for example, within the optional range, the solubility parameter is higher and the solubility performance is improved.

[0188] For example, R 23 Including substituted or unsubstituted C5 straight chain alkyl, C6 straight chain alkyl, C7 straight chain alkyl, C8 straight chain alkyl, C9 straight chain alkyl, C10 straight chain alkyl, C11 straight chain alkyl, C12 straight chain alkyl, C13 straight chain alkyl, C14 straight chain alkyl, C15 straight chain alkyl, C16 straight chain alkyl, C17 straight chain alkyl, C18 straight chain alkyl, C19 straight chain alkyl, C20 straight chain alkyl or a range consisting of any two of the above values.

[0189] In some embodiments, R 21 and R 22 The same groups can be included to simplify the reaction process. 21 and R 22 They may also be different groups.

[0190] Exemplarily, the perovskite solar cell material includes at least one of the compounds represented by formula (X-11) to the compounds represented by formula (X-17),

[0191]

[0192]

[0193]

[0194]

[0195] In some embodiments, R 21 and R 22 Each independently includes an alkyl-substituted aryl group, wherein the alkyl-substituted aryl group includes the structural formula shown in formula (F),

[0196]

[0197] R 24 It can be a branched alkyl group or a straight-chain alkyl group, and can be a straight-chain alkyl group. The steric hindrance of the straight-chain alkyl group is relatively smaller, which is more conducive to the compound forming a dense film layer. 24 A substituted or unsubstituted C5 to C20 straight chain alkyl group may be included.

[0198] R 24 Including substituted or unsubstituted C6 to C16 straight chain alkyl groups; the adjustment of the chain length of the above group can adjust its solubility parameter in the halogenated solvent, for example, the solubility parameter is higher within the optional range, and the solubility performance is improved. Moreover, the adjustment of the chain length of the above group can adjust the energy level of the compound and the distribution of the electron cloud, so that the compound and the energy level of the perovskite absorption layer are more matched.

[0199] For example, R 24 Including substituted or unsubstituted C5 straight chain alkyl, C6 straight chain alkyl, C7 straight chain alkyl, C8 straight chain alkyl, C9 straight chain alkyl, C10 straight chain alkyl, C11 straight chain alkyl, C12 straight chain alkyl, C13 straight chain alkyl, C14 straight chain alkyl, C15 straight chain alkyl, C16 straight chain alkyl, C17 straight chain alkyl, C18 straight chain alkyl, C19 straight chain alkyl, C20 straight chain alkyl or a range consisting of any two of the above values.

[0200] Adjustment of the chain length of the above groups can adjust their solubility parameters in halogenated solvents. For example, within the optional range, the solubility parameter is higher and the solubility performance is improved.

[0201] R 24It can be grafted at the para, ortho or meta position of the benzene ring. Optionally, the alkyl-substituted aryl group includes the structural formula shown in formula (F-1),

[0202]

[0203] The alkyl group at the para position has less steric hindrance than the ortho / meta positions and has the least effect on the planarity of the overall compound.

[0204] In some embodiments, R 21 and R 22 Including the same group is beneficial to simplify the reaction process. 21 and R 22 They may also be different groups.

[0205] Exemplarily, the perovskite solar cell material includes at least one of the compounds represented by formula (X-21) to the compounds represented by formula (X-28),

[0206]

[0207]

[0208]

[0209]

[0210]

[0211] Electron transport materials

[0212] In the second aspect, the embodiment of the present application proposes an electron transport material, and the electron transport material includes at least one of the compound shown in formula (Z) and the compound shown in formula (X) of any embodiment of the first aspect of the present application. The above-mentioned electron transport material is conducive to forming a dense electron transport layer, which can reduce the number of ions migrating to the electrode, improve the device structure stability of the perovskite solar cell, and improve the energy conversion efficiency of the perovskite solar cell; and the film layer also has a certain hydrophobicity, which can play a certain barrier role to external water and oxygen while blocking the migration of ions, reduce the risk of water and oxygen eroding the perovskite absorption layer and causing perovskite degradation, further improve the device structure stability, and further improve the energy conversion efficiency of the perovskite solar cell.

[0213] Perovskite solar cells

[0214] In a third aspect, an embodiment of the present application proposes a perovskite solar cell.

[0215] like Figure 1As shown, the perovskite solar cell 1 includes a perovskite absorption layer 10, a hole transport layer 20 and an electron transport layer 30. The hole transport layer 20 is arranged on one side of the perovskite absorption layer 10, and the electron transport layer 30 is arranged on the side of the perovskite absorption layer 10 away from the hole transport layer 20. The electron transport layer 30 may include the electron transport material of any embodiment of the second aspect of the present application.

[0216] As a transport layer, the electron transport layer 30 can effectively transport electrons, reduce carrier recombination at the interface between the perovskite absorption layer and the electron transport layer, and improve the energy conversion efficiency of the perovskite solar cell 1.

[0217] In some embodiments, the thickness of the electron transport layer 30 is from 10 nm to 200 nm.

[0218] Exemplarily, the thickness of the electron transport layer 30 can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, or a range consisting of any two of the above values.

[0219] The perovskite material in the perovskite absorption layer refers to a metal oxide with a perovskite structure, and its crystal structure is ABX3, A and B are cations, X is an anion, and in an ideal cubic structure, the B cation has a 6-fold coordination and is surrounded by an anion octahedron, and the A cation has a 12-fold cubic octahedral coordination. The cubic unit cell of this compound is composed of A cations located at the corner positions of the cube, B located at the body center position, and X anions occupying the face center position. For example, the perovskite material includes at least one of CH3NH3PbI3, CH3NH3PbBr3, CsPbBr3, CsPbI3, and CH(NH2)2PbI3 (FAPbI3).

[0220] After the perovskite material absorbs photons, electron-hole pairs are generated, which are thermalized to form excitons. Then charge separation occurs, and the photogenerated electrons jump to the LUMO energy level of the perovskite absorption layer, and the photogenerated holes jump to the HOMO energy level of the perovskite absorption layer.

[0221] Perovskite solar cells can be in either a normal structure (nip) or a transverse structure (pin).

[0222] The formal structure of the perovskite solar cell includes a transparent conductive electrode, an electron transport layer, a perovskite absorption layer, a hole transport layer and a metal electrode stacked in sequence along its own thickness direction. Exemplarily, the transparent conductive electrode includes indium tin oxide ITO or fluorine-doped tin oxide FTO. The hole transport layer includes 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), polymer poly(3-hexylthiophene) (P3HT), poly(triarlyamine) (PTAA), etc. The metal electrode includes a gold layer, a silver layer or an aluminum layer. Optionally, a functional layer structure such as a buffer layer and a passivation layer may be further included between the transport layer and the perovskite absorption layer.

[0223] The inverted structure perovskite solar cell includes a transparent conductive electrode, a hole transport layer, a perovskite absorption layer, an electron transport layer and a metal electrode stacked in sequence along its own thickness direction. Exemplarily, the transparent conductive electrode includes an indium tin oxide ITO layer or a fluorine-doped tin oxide FTO layer. The hole transport layer includes a PEDOT:PSS layer, PTAA and NiOx, wherein PEDOT represents a polymer of EDOT (3,4-ethylenedioxythiophene monomer) and PSS represents polystyrene sulfonate. The metal electrode includes a gold layer, a silver layer or an aluminum layer. The preparation process of a solar cell of this structure is relatively simple. Optionally, a functional layer structure such as a buffer layer and a passivation layer may be further included between the transport layer and the perovskite absorption layer.

[0224] Passivation materials

[0225] In a fourth aspect, an embodiment of the present application proposes a passivation material, the passivation material comprising at least one of the compound represented by formula (Z) and the compound represented by formula (X) of any embodiment of the first aspect of the present application. The above-mentioned passivation material can reduce the number of ions migrating to the electrode, improve the device structure stability of the perovskite solar cell, and improve the energy conversion efficiency of the perovskite solar cell; and the film layer also has a certain hydrophobicity, which can play a certain barrier role to external water and oxygen while blocking the migration of ions, reduce the risk of water and oxygen eroding the perovskite absorption layer and causing perovskite degradation, further improve the device structure stability, and further improve the energy conversion efficiency of the perovskite solar cell.

[0226] Perovskite solar cells

[0227] In a fifth aspect, an embodiment of the present application proposes a perovskite solar cell.

[0228] like Figure 2As shown, the perovskite solar cell 1 includes a perovskite absorption layer 10, a hole transport layer 20, an electron transport layer 30 and a passivation layer 40. The hole transport layer 20 is arranged on one side of the perovskite absorption layer 10, the electron transport layer 30 is arranged on the side of the perovskite absorption layer 10 away from the hole transport layer 20, and the passivation layer 40 is arranged between the perovskite absorption layer 10 and the electron transport layer 30. The passivation layer 40 may include the passivation material of any embodiment of the fourth aspect of the present application.

[0229] In some embodiments, the thickness of the passivation layer 40 is 1 nm to 20 nm.

[0230] Exemplarily, the thickness of the passivation layer 40 may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or a range consisting of any two of the above values.

[0231] In some embodiments, the perovskite material in the perovskite absorber layer 10 may include at least one of CH3NH3PBI3, CH3NH3PBBr3, CsPbBr3, CsPbI3, CH(NH2)2PbI3 (FAPbI3).

[0232] Perovskite solar cells can be in either a normal structure (nip) or a transverse structure (pin).

[0233] The formal structure of the perovskite solar cell includes a transparent conductive electrode, an electron transport layer, a passivation layer, a perovskite absorption layer, a hole transport layer and a metal electrode stacked in sequence along its own thickness direction. Exemplarily, the transparent conductive electrode includes indium tin oxide ITO or fluorine-doped tin oxide FTO. The electron transport layer includes materials such as titanium oxide and tin oxide. The hole transport layer includes 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), polymer poly(3-hexylthiophene) (P3HT), poly(triarlyamine) (PTAA), etc. The metal electrode includes a gold layer, a silver layer or an aluminum layer.

[0234] The inverted structure perovskite solar cell includes a transparent conductive electrode, a hole transport layer, a perovskite absorption layer, a passivation layer, an electron transport layer and a metal electrode which are sequentially stacked along its own thickness direction. Exemplarily, the transparent conductive electrode includes an indium tin oxide ITO layer or a fluorine-doped tin oxide FTO layer. The hole transport layer includes a PEDOT:PSS layer, PTAA and NiOx, wherein PEDOT represents a polymer of EDOT (3,4-ethylenedioxythiophene monomer) and PSS represents polystyrene sulfonate. The electron transport layer includes a fullerene derivative ([6,6]-phenyl-C61-butyric acid methyl ester) layer or a C60 layer. The metal electrode includes a gold layer, a silver layer or an aluminum layer. The preparation process of a solar cell of this structure is relatively simple.

[0235] Photovoltaic modules

[0236] The sixth aspect of the present application further provides a photovoltaic module, comprising the perovskite solar cell of any embodiment of the third aspect of the present application, or the perovskite solar cell of the method of the fourth aspect of the present application.

[0237] In some embodiments, a photovoltaic module may include at least one perovskite solar cell, for example, a photovoltaic module may include one perovskite solar cell, or include multiple perovskite solar cells, and in the case where the photovoltaic module includes multiple perovskite solar cells, the multiple perovskite solar cells can be connected in series, in parallel, or in a hybrid manner. Hybrid means that multiple perovskite solar cells are divided into multiple groups of cells, each group of cells is connected in series, and then two adjacent groups of cells are connected in parallel; or each group of cells is connected in parallel, and then two adjacent groups of cells are connected in series.

[0238] Electrical devices

[0239] The seventh aspect of the present application further provides an electrical device, comprising a photovoltaic component according to any embodiment of the sixth aspect of the present application.

[0240] The photovoltaic module can be used as a power source for the electrical device or as an energy storage unit of the photovoltaic module. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0241] Figure 3 2 is a schematic diagram of an exemplary electric device 2. The electric device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. The electric device 2 includes a perovskite solar cell 1.

[0242] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc.

[0243] Example

[0244] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0245] Example 1

[0246] Synthesis of the compound represented by formula (X-11)

[0247] Synthesis of M2 (Grignard reaction):

[0248] Preparation of Grignard reagent: Under nitrogen (N2) protection, add 2, bromo-5, decylthiophene (3.00 g, 9.89 mmol) and magnesium chips (0.25 g, 10.29 mmol) into a flask, then inject 15 mL of tetrahydrofuran (THF) to remove water and oxygen and 1.5 mL of dichloromethane (CH2Cl2), then add two drops of 1,2-dibromoethane to initiate the reaction, reflux at 70°C for 2 hours, and then cool to room temperature.

[0249] Under 0℃ / N2 protection, M1 (4.04 g, 9.89 mmol) was dissolved in 100 mL of THF from which water and oxygen had been removed, and the above-mentioned Grignard reagent was added to the reaction system with a double needle. After stirring for 1.5 h, the mixture was heated to room temperature and reacted for 24 h. After the reaction was completed, the reaction solution was poured into a saturated aqueous ammonium chloride solution, extracted with THF, the organic phase was separated, dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation to obtain 7.73 g of crude product.

[0250] Under N2 protection, all the crude products and anhydrous stannous chloride (3.80 g, 20.04 mmol) were added to 350 mL of toluene from which water and oxygen had been removed, and the temperature was raised to 85°C for 4 h. After the reaction, the reaction solution was dried by rotary evaporation and purified by column chromatography (volume ratio of eluent, petroleum ether: CH2Cl2 = 1:1) to obtain 5.70 g of powdered solid with a yield of 70%.

[0251] Synthesis of M3 (acylation reaction):

[0252] Under N2 protection, M2 (5.00 g, 6.07 mmol) and 150 mL of THF dehydrated with water and oxygen were added to the flask, cooled to -78 °C, and n-butyl lithium (n-BuLi) in n-hexane solution (3.0 mL, 2.50 mol / L) was slowly added to the reaction solution. After the addition was completed, the mixture was stirred at -78 °C for 1 h, and then DMF (0.95 mL, 12.32 mmol) dehydrated with water and oxygen was added, and the mixture was stirred at -78 °C for 1 h, and then heated to room temperature and stirred for 24 h. After the reaction was completed, water was added to quench the reaction, and the reaction solution was poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated, dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 2:1) to obtain 3.79 g of powdered solid with a yield of 71%.

[0253] Synthesis of X-11 (aldol condensation reaction):

[0254] Under N2 protection, M3 (3.00 g, 3.41 mmol) and sulfone indanone (1.27 g, 6.99 mmol) were added to the flask, and then 100 mL of acetic anhydride was injected, and the temperature was raised to 110 ° C and stirred for 24 hours. After the reaction was completed, the reaction solution was cooled to room temperature, poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated and dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 1:1) to obtain 0.94 g of powdered solid with a yield of 23%. 1 H NMR (400MHz, Chloroform-d): δ9.35(s,2H),8.78(s,2H),8.14(td,J=7.6,2.5Hz,2H),8.04–7.87(m,8H),7.33(dd,J=8 .0,2.0Hz,2H),2.43(t,J=7.4Hz,4H),1.65(td,J=7.3,6.1Hz,4H),1.38–1.13(m,27H),0.88(s,1H),0.88–0.83(m,6H).

[0255] The reaction mechanism is as follows:

[0256]

[0257] Synthesis of the compound represented by formula (X-12), the compound represented by formula (X-13), and the compound represented by formula (X-14): Use similar synthesis steps to the compound represented by formula (X-11).

[0258]

[0259] Analysis of X-12's NMR spectrum: 1H NMR (400MHz, Chloroform-d): δ8.86(s,2H,),8.26(s,2H),7.74-7.91(m,6H),7.57-7.70(m,4H),7.31(d,J =8.0Hz, 2H), 2.45 (t, J = 7.4Hz, 4H), 1.66 (t, J = 7.4, 6.6Hz, 4H), 1.16-1.34 (m, 28H), 0.87 (t, J = 7.0Hz, 6H).

[0260] Analysis of X-13's NMR spectrum: 1 H NMR (400MHz, Chloroform-d): δ9.34(s,1H),8.87(s,1H),8.78(s,1H),8.26(s,1H),7.77-8.21(m,8 H),7.57-7.70(m,2H),7.26-7.38(m,2H),1.59-1.73(m,4H),1.16-1.34(m,28H),0.81-0.92(m,6H).

[0261] Analysis of X-14's NMR spectrum: 1 H NMR (400MHz, Chloroform-d): δ8.83(s,2H),8.17-8.29(m,6H),7.79(d,J=8.0Hz,2H),7.31(d,J=8.0H z, 2H), 2.46 (t, J = 7.4Hz, 4H), 1.66 (tt, J = 7.4, 6.6Hz, 4H), 1.16-1.34 (m, 28H), 0.87 (t, J = 7.0Hz, 6H).

[0262] Example 2

[0263] Synthesis of the compound represented by formula (X-21)

[0264] Synthesis of M5:

[0265] Preparation of Grignard reagent: Under N2 protection, 1, bromo-4, alkylbenzene (2.00 g, 6.73 mmol) and magnesium chips (0.18, 7.41 mmol) were added to the flask, followed by injection of 15 mL of THF to remove water and oxygen and 1.5 mL of CH2Cl2, and then two drops of 1,2-dibromoethane were added to initiate the reaction, refluxed at 70°C for 2 h, and then cooled to room temperature.

[0266] Under 0℃ / N2 protection, M1 (2.75g, 6.73mmol) was dissolved in 75mL of THF to remove water and oxygen, and the above-mentioned Grignard reagent was added to the reaction system with a double needle. After stirring for 1.5h, the temperature was raised to room temperature and the reaction was continued for 24h. After the reaction was completed, the reaction solution was poured into a saturated aqueous ammonium chloride solution, extracted with THF, and the organic phase was separated. The water was removed with anhydrous Na2SO4, filtered and dried by rotary evaporation to obtain 4.92g of crude product.

[0267] Under N2 protection, all the crude products and anhydrous stannous chloride (2.56 g, 13.50 mmol) were added to 180 mL of toluene from which water and oxygen had been removed, and the temperature was raised to 85°C for 4 h. After the reaction, the reaction solution was dried by rotary evaporation and purified by column chromatography (petroleum ether: CH2Cl2 = 1:1) to obtain 2.78 g of powdered solid with a yield of 51%.

[0268] Synthesis of M6:

[0269] Under N2 protection, M5 (2.50 g, 3.08 mmol) and 70 mL of THF dehydrated with water and oxygen were added to the flask, cooled to -78 °C, and n-BuLi n-hexane solution (1.40 mL, 2.50 mol / L) was slowly added to the reaction solution. After the addition was completed, the mixture was stirred at -78 °C for 1 h, and then DMF (0.49 mL, 6.35 mmol) dehydrated with water and oxygen was added, and the mixture was stirred at -78 °C for 1 h, and then heated to room temperature and stirred for 24 h. After the reaction was completed, water was added to quench the reaction, and the reaction solution was poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated, dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 2:1) to obtain 1.73 g of powdered solid with a yield of 65%.

[0270] Compound represented by formula (X-21):

[0271] Under N2 protection, M6 (1.00 g, 1.15 mmol) and sulfone indanone (420.17 mg, 2.31 mmol) were added to the flask, and then 35 mL of acetic anhydride was injected, and the temperature was raised to 110 ° C and stirred for 24 hours. After the reaction was completed, the reaction solution was cooled to room temperature, poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated and dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 1:1) to obtain 0.29 g of powdered solid with a yield of 21%. 1H NMR (400MHz, Chloroform-d): δ9.38 (s, 2H), 8.99 (ddd, J=9.8, 7.9, 1.7Hz, 2H), 8.80 (s, 2H), 8.14 (td, J=7.6, 2.5Hz, 2H), 8.04–7.96 (m, 4H), 7 .96–7.86(m,4H),7.40–7.26(m,4H),2.29(t,J=7.2Hz,4H),1.81–1.69 (m,4H),1.35–1.18(m,27H),0.91(d,J=2.1Hz,1H),0.88–0.84(m,6H).

[0272] The reaction mechanism is as follows:

[0273]

[0274] Synthesis of the compound represented by formula (X-22) and the compound represented by formula (X-23): Use similar synthesis steps as the compound represented by formula (X-21).

[0275]

[0276] Analysis of X-22's NMR spectrum: 1 H NMR (400MHz, Chloroform-d): δ8.91(s,2H),8.57(s,2H),8.26(ddd,J=8.1,1.9,0.4Hz,4H),7.77-7.91(m,4H),7.57-7.69(m,4H) ,7.23(ddd,J=8.1,1.5,0.4Hz,4H),2.28(t,J=7.2Hz,4H),1.75(tt,J=7.2,7.0Hz,4H),1.16-1.34(m,28H),0.87(t,J=7.0Hz,6H).

[0277] Analysis of X-23's NMR spectrum: 1 H NMR (400MHz, Chloroform-d): δ8.88(s,2H),8.56(s,2H),8.17-8.31(m,8H),7.20(ddd,J=8.1,1.5,0.4 Hz, 4H), 2.29 (t, J = 7.4Hz, 4H), 1.75 (tt, J = 7.4, 7.0Hz, 4H), 1.16-1.34 (m, 28H), 0.87 (t, J = 7.0Hz, 6H).

[0278] Example 3

[0279] Synthesis of the compound represented by formula (Z-11)

[0280] Synthesis of M8:

[0281] Preparation of Grignard reagent: Under N2 protection, add 2, bromo-5, decylthiophene (2.00 g, 6.58 mmol) and magnesium turnings (0.17 g, 6.86 mmol) into a flask, then inject 10 mL of tetrahydrofuran (THF) to remove water and oxygen and 1 mL of dichloromethane (CH2Cl2), then add two drops of 1,2-dibromoethane to initiate the reaction, reflux at 70°C for 2 h, and then cool to room temperature.

[0282] Under 0℃ / N2 protection, M7 (1.95g, 6.58mmol) was dissolved in 50mL of THF to remove water and oxygen, and the above-mentioned Grignard reagent was added to the reaction system with a double needle. After stirring for 1.5h, the temperature was raised to room temperature and the reaction was continued for 24h. After the reaction was completed, the reaction solution was poured into a saturated aqueous ammonium chloride solution, extracted with THF, and the organic phase was separated. The water was removed with anhydrous Na2SO4, and the mixture was filtered and dried by rotary evaporation to obtain 4.36g of crude product.

[0283] Under N2 protection, all the crude products and anhydrous stannous chloride (2.56 g, 13.50 mmol) were added to 180 mL of toluene from which water and oxygen had been removed, and the temperature was raised to 85°C for 4 h. After the reaction, the reaction solution was dried by rotary evaporation and purified by column chromatography (petroleum ether: CH2Cl2 = 1:1) to obtain 2.76 g of powdered solid with a yield of 59%.

[0284] Synthesis of M9:

[0285] Under N2 protection, M8 (2.50 g, 3.52 mmol) and 70 mL of THF dehydrated with water and oxygen were added to the flask, cooled to -78 °C, and n-BuLi n-hexane solution (1.4 mL, 2.50 mol / L) was slowly added to the reaction solution. After the addition was completed, the mixture was stirred at -78 °C for 1 h, and then DMF (0.55 mL, 7.15 mmol) dehydrated with water and oxygen was added, and the mixture was stirred at -78 °C for 1 h, and then heated to room temperature and stirred for 24 h. After the reaction was completed, water was added to quench the reaction, and the reaction solution was poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated, dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 3:1) to obtain 2.02 g of powdered solid with a yield of 75%.

[0286] Synthesis of Z-11:

[0287] Under N2 protection, M9 (2.00 g, 2.61 mmol) and sulfone indanone (974.86 mg, 5.35 mmol) were added to the flask, and then 70 mL of acetic anhydride was injected, and the temperature was raised to 110 ° C and stirred for 24 hours. After the reaction was completed, the reaction solution was cooled to room temperature, poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated and dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 2:1) to obtain 0.51 g of powdered solid with a yield of 18%. 1 H NMR (400MHz, Chloroform-d): δ9.37(s,2H),8.77(d,J=0.8Hz,2H),8.16(ddd,J=7.7,6.8,2.5Hz,2H),8.06–7.93(m,6H),7.87(dd,J=8.0,5.2 Hz,2H),7.35(dd,J=8.0,2.8Hz,2H),2.49(t,J=7.4Hz,4H),1.72–1.60(m,4H),1.37–1.14(m,27H),0.91(d,J=2.1Hz,1H),0.88–0.84(m,6H).

[0288] The reaction mechanism is as follows:

[0289]

[0290]

[0291] Synthesis of the compound represented by formula (Z-12) and the compound represented by formula (Z-13): Use similar synthesis steps as the compound represented by formula (Z-11).

[0292]

[0293] Analysis of Z-12's NMR spectrum: 1 H NMR (400MHz, Chloroform-d): δ8.87(s,2H),8.66(s,2H),7.59-7.92(m,10H),7.33(d,J=8.0Hz,2 H), 2.50 (t, J = 7.4Hz, 4H), 1.66 (tt, J = 7.4, 6.6Hz, 4H), 1.16-1.34 (m, 28H), 0.87 (t, J = 7.0Hz, 6H).

[0294] Analysis of Z-13's NMR spectrum: 1H NMR (400MHz, Chloroform-d): δ8.84(s,2H),8.65(s,2H),8.07-8.17(m,4H),7.73(d,J=8.0Hz,2H),7.33(d, J=8.0Hz,2H),2.50(t,J=7.4Hz,4H),1.66(tt,J=7.4,6.6Hz,4H),1.16-1.34(m,28H),0.87(t,J=7.0Hz,6H).

[0295] Example 4

[0296] Synthesis of the compound represented by formula (Z-21)

[0297] Synthesis of M11:

[0298] Preparation of Grignard reagent: Under N2 protection, 1, bromo-4, alkylbenzene (2.00 g, 6.73 mmol) and magnesium chips (0.18, 7.41 mmol) were added to the flask, followed by injection of 15 mL of THF to remove water and oxygen and 1.5 mL of CH2Cl2, and then two drops of 1,2-dibromoethane were added to initiate the reaction, refluxed at 70°C for 2 h, and then cooled to room temperature.

[0299] Under 0℃ / N2 protection, M7 (1.99 g, 6.73 mmol) was dissolved in 50 mL of THF from which water and oxygen had been removed, and the above-mentioned Grignard reagent was added to the reaction system with a double needle. After stirring for 1.5 h, the mixture was heated to room temperature and reacted for 24 h. After the reaction was completed, the reaction solution was poured into a saturated aqueous ammonium chloride solution, extracted with THF, and the organic phase was separated. The water was removed with anhydrous Na2SO4, filtered and dried by rotary evaporation to obtain 4.38 g of crude product.

[0300] Under N2 protection, all the crude products and anhydrous stannous chloride (2.56 g, 13.50 mmol) were added to 180 mL of toluene from which water and oxygen had been removed, and the temperature was raised to 85°C for 4 h. After the reaction, the reaction solution was dried by rotary evaporation and purified by column chromatography (petroleum ether: CH2Cl2 = 1:1) to obtain 2.26 g of powdered solid with a yield of 48%.

[0301] Synthesis of M12:

[0302] Under N2 protection, M11 (2.20 g, 3.15 mmol) and 65 mL of THF dehydrated with water and oxygen were added to the flask, cooled to -78 ° C, and n-BuLi n-hexane solution (1.3 mL, 2.50 mol / L) was slowly added to the reaction solution. After the addition was completed, it was kept at -78 ° C and stirred for 1 h, and then DMF (0.49 mL, 6.45 mmol) dehydrated with water and oxygen was added, and continued to stir at -78 ° C for 1 h, and then the temperature was raised to room temperature and stirred for 24 h. After the reaction was completed, water was added to quench the reaction, and the reaction solution was poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated. It was dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (pure petroleum ether) to obtain 1.47 g of powdered solid with a yield of 62%.

[0303] Synthesis of Z-21:

[0304] Under N2 protection, M12 (1.47 g, 1.95 mmol) and sulfone indanone (728.34 mg, 4.00 mmol) were added to the flask, and then 51 mL of acetic anhydride was injected, and the temperature was raised to 110°C and stirred for 24 hours. After the reaction was completed, the temperature was lowered to room temperature, and the reaction solution was poured into a saturated saline solution, extracted with CH2Cl2, and the organic phase was separated and dehydrated with anhydrous Na2SO4, filtered and dried by rotary evaporation, and then purified by column chromatography (petroleum ether: CH2Cl2 = 2:1) to obtain 0.49 g of powdered solid with a yield of 23%. 1 H NMR (400MHz, Chloroform-d): δ9.40(s,2H),9.00(ddd,J=11.7,8.0,1.6Hz,2H),8.79(d,J=2.0Hz,2H),8.16(ddd,J=7.7,6.8,2.6Hz,2H) ,8.09–7.86(m,8H),7.44–7.28(m,4H),2.32(t,J=7.2Hz,4H),1.73(p,J=7.1Hz,4H),1.33–1.20(m,27H),0.88(s,1H),0.88–0.82(m,6H).

[0305] The reaction mechanism is as follows:

[0306]

[0307] Synthesis of the compound represented by formula (Z-22) and the compound represented by formula (Z-23): Use similar synthesis steps as the compound represented by formula (Z-21).

[0308]

[0309] Analysis of Z-22's NMR spectrum: 1H NMR (400MHz, Chloroform-d): δ8.92(s,2H),8.68(s,2H),8.28(ddd,J=8.1,1.8,0.4Hz,4H),7.78-7.92(m,4H),7.58-7.71(m,4H) ,7.20(ddd,J=8.1,1.5,0.4Hz,4H),2.32(t,J=7.4Hz,4H),1.73(tt,J=7.4,7.0Hz,4H),1.16-1.34(m,28H),0.87(t,J=7.0Hz,6H).

[0310] Analysis of Z-23's NMR spectrum: 1 H NMR (400MHz, Chloroform-d): δ8.89(s,2H),8.67(s,2H),8.28(ddd,J=8.1,1.8,0.4Hz,4H),8.07-8.17(m,4H),7.22(dd d,J=8.1,1.5,0.4Hz,4H),2.32(t,J=7.4Hz,4H),1.73(tt,J=7.4,7.0Hz,4H),1.16-1.34(m,28H),0.87(t,J=7.0Hz,6H).

[0311] Example 5

[0312] Perovskite solar cell device preparation (the compound shown in formula (Z) is used as the electron transport layer):

[0313] Device structure: FTO / NiO x / CH3NH3PbI3 / electron transport layer / Ag

[0314] (1) FTO (fluorine-doped SnO2) conductive glass cleaning

[0315] The etched FTO glass was ultrasonically cleaned in an aqueous solution of a surfactant, distilled water, acetone and alcohol for 30 minutes respectively, and finally dried with nitrogen for later use.

[0316] (2) Preparation of NiOx hole transport layer

[0317] NiOx was prepared as hole transport layer material by magnetron sputtering.

[0318] The above FTO glass was placed in a vacuum chamber and the vacuum degree was pumped to 3×10 -4 Pa, and then the sputtering power was 70 W, the sputtering intensity was 0.3 Pa, and the sputtering time was 10 min to prepare a NiOx film with a thickness of 30 nm as a hole transport layer.

[0319] (3) Preparation of CH3NH3PbI3 perovskite layer

[0320] Preparation of perovskite precursor solution: MAI powder, PbI2 powder and lead acetate powder were mixed in a ratio of 2.2 mmol: 0.4 mmol: 0.6 mmol, and the mixture was added into 1 mL DMF and magnetically stirred for 6 hours.

[0321] Then in the glove box, 35 μL of CH3NH3PbI3 perovskite precursor solution was added to the upper surface of the substrate coated with the NiOx hole transport layer and spin coating was started at 4000 rpm for 30 seconds. After spin coating, it was transferred to a hot stage at 100°C for annealing and crystallization for 10 minutes to obtain a uniform and dense perovskite film as a perovskite absorption layer.

[0322] (4) Preparation of electron transport layer and Ag electrode

[0323] Before the experiment, a 20 mg / mL solution of the compound represented by formula (X-11) was prepared (chlorobenzene was used as the solvent).

[0324] After 40 μL of the solution of the compound represented by formula (X-11) was dropped onto the substrate coated with the perovskite film, spin coating was started at 1500 rpm for 30 seconds. After spin coating, it was transferred to a hot stage at 70°C for annealing and crystallization for 10 minutes.

[0325] Transfer the spin-coated device to the evaporation chamber, put the silver particles into the evaporation boat, and close the chamber door. Evacuate to 10 - 4 Pa, A 100nm thick silver electrode is evaporated at a speed of , and taken out after the vacuum is stopped, thus completing the preparation of the perovskite solar cell.

[0326] Comparative Example 1

[0327] The perovskite solar cell was prepared by a method similar to that of Example 5-1, except that the material of the electron transport layer was C 60 Solution (chlorobenzene as solvent).

[0328] Example 5-2 to Example 5-13

[0329] A perovskite solar cell was prepared using a method similar to that of Example 5-1, except that the material of the electron transport layer was adjusted.

[0330] Battery performance test:

[0331] IV measurement method (test equipment: solar cell IV tester):

[0332] By changing the bias voltage point and measuring the current at the same time, the IV characteristics (current-voltage curve) of the sample under test can be obtained.

[0333] a) Place the test fixture with the sample battery on the sample holder so that it is located in the measurement plane and ensure that the sample battery is located at the center of the solar simulator's output light spot (or the normal line of the photovoltaic cell is parallel to the center line of the solar simulator's light source output light beam);

[0334] b) at 1000W / m 2 Under the irradiance condition, a mask is installed on the sample battery to be tested, and the temperature of the sample battery is controlled by a temperature monitoring device so that the temperature of the sample to be tested is maintained at (30±5℃) during the measurement process;

[0335] c) Set the scanning direction, voltage range, scanning interval voltage and scanning interval time, etc. It is recommended that the scanning interval should not be greater than 0.02V, and the interval between two adjacent points should not be less than 0.3s. Measure the forward and reverse scanning current-voltage characteristics of the sample battery under test, and record the open circuit voltage Voc and short circuit current Jsc.

[0336] Calculation formula: Fill factor FF = Jm*Vm / Voc*Jsc, energy conversion efficiency PCE = Voc*Jsc*FF / Pin. Pin is the incident light intensity, which can be 10 3 W / m 2 .

[0337] V OC Expressed as open circuit voltage. J SC Expressed as short-circuit current. FillFactor is the filling factor. PCE stands for "Power conversion efficiency" in English and "energy conversion efficiency" in Chinese.

[0338] Test Results

[0339] Table 1

[0340]

[0341] It can be seen from Table 1 that the compounds in the examples of the present application are used as electron transport layer materials to improve device performance.

[0342] Example 6-1

[0343] Perovskite solar cell device preparation (the compound shown in formula (X-11) is used as the passivation layer material):

[0344] Device structure: FTO / NiO x / CH3NH3PbI3 / passivation layer / C 60 / Ag

[0345] (1) FTO conductive glass cleaning

[0346] The etched FTO glass was ultrasonically cleaned in an aqueous solution of a surfactant, distilled water, acetone and alcohol for 30 minutes respectively, and finally dried with nitrogen for later use.

[0347] (2) Preparation of NiOx hole transport layer

[0348] NiOx was prepared as hole transport layer material by magnetron sputtering.

[0349] The above FTO glass was placed in a vacuum chamber and the vacuum degree was pumped to 3×10 -4 Pa, and then the sputtering power was 70 W, the sputtering intensity was 0.3 Pa, and the sputtering time was 10 min to prepare a NiOx film with a thickness of 30 nm as a hole transport layer.

[0350] (3) Preparation of CH3NH3PbI3 perovskite layer

[0351] Preparation of perovskite precursor solution: MAI powder, PbI2 powder and lead acetate powder were mixed in a ratio of 2.2 mmol: 0.4 mmol: 0.6 mmol, and the mixture was added into 1 mL DMF and magnetically stirred for 6 hours.

[0352] Then in the glove box, 35 μL of CH3NH3PbI3 perovskite precursor solution was added to the upper surface of the substrate coated with the NiOx hole transport layer and spin coating was started at 4000 rpm for 30 seconds. After spin coating, it was transferred to a hot stage at 100°C for annealing and crystallization for 10 minutes to obtain a uniform and dense perovskite film as a perovskite absorption layer.

[0353] (4) Preparation of passivation layer, electron transport layer and Ag electrode

[0354] 40 μL of a solution of the compound represented by formula (X-11) (chlorobenzene as solvent) was dripped onto the device with the perovskite absorption layer spin-coated, and the device was spin-coated at 3000 rpm for 30 seconds. After the spin-coating, the device was annealed at 70° C. for 10 minutes to form a passivation layer. The device was cooled to room temperature and then used for later use.

[0355] 40 μL of C was added dropwise onto the substrate coated with the passivation layer. 60 The spin coating was started after adding a solution (chlorobenzene as solvent) at 1500 rpm for 30 seconds. After spin coating, it was transferred to a hot stage at 70°C for annealing and crystallization for 10 minutes.

[0356] Transfer the spin-coated device to the evaporation chamber, put the silver particles into the evaporation boat, and close the chamber door. Evacuate to 10 - 4 Pa, A 100nm thick silver electrode is evaporated at a speed of , and taken out after the vacuum is stopped, thus completing the preparation of the perovskite solar cell.

[0357] Example 6-2 to Example 6-6

[0358] A perovskite solar cell was prepared using a method similar to that of Example 6-1, except that the material of the passivation layer was adjusted.

[0359] Test Results

[0360] Table 2

[0361]

[0362]

[0363] It can be seen from Table 2 that the compounds shown in the examples of the present application, as passivation layer materials, improve the device performance.

[0364] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A material for a perovskite solar cell, comprising at least one of a compound represented by formula (Z) and a compound represented by formula (X), In formula (Z), R 11 and R 12 Each independently includes an alkyl-substituted thiophene group or an alkyl-substituted aryl group, wherein the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group; Y 11 and Y 12 Each independently includes a conjugated group; In formula (X), R 21 and R 22 Each independently includes an alkyl-substituted thiophene group, an alkyl-substituted aryl group, wherein the alkyl group is a substituted or unsubstituted C5 to C20 alkyl group; Y 21 and Y 22 Each independently includes conjugated groups.

2. The perovskite solar cell material according to claim 1, wherein: Y 11 and Y 12 Each independently includes an aryl derivative; optionally, Y 11 and Y 12 Each independently comprises the structural formula represented by formula (A), In formula (A), M1 and M2 each independently include At least one of; M3 includes at least one of a hydrogen atom and a halogen atom; alternatively, M3 includes a hydrogen atom or a halogen atom; Further optionally, Y 11 and Y 12 Each independently comprises at least one of the structural formulas represented by formula (A-1) to formula (A-9), 3. The perovskite solar cell material according to claim 1 or 2, wherein: R 11 and R 12 Each independently includes an alkyl-substituted thiophene group, wherein the alkyl-substituted thiophene group includes the structural formula shown in formula (C), R 13 including substituted or unsubstituted C6 to C16 straight chain alkyl groups; Further optionally, R 11 and R 12 The same groups are included.

4. The perovskite solar cell material according to any one of claims 1 to 3, wherein The perovskite solar cell material comprises at least one of the compounds represented by formula (Z-11) to the compounds represented by formula (Z-18), 5. The perovskite solar cell material according to any one of claims 1 to 4, wherein R 11 and R 12 Each independently includes an alkyl-substituted aryl group, wherein the alkyl-substituted aryl group includes the structural formula shown in formula (D), R 14 including substituted or unsubstituted C6 to C16 straight chain alkyl groups; Optionally, the alkyl-substituted aryl group includes the structural formula shown in formula (D-1), Further optionally, R 11 and R 12 The same groups are included.

6. The material for a perovskite solar cell according to any one of claims 1 to 5, wherein The perovskite solar cell material comprises at least one of the compounds represented by formula (Z-21) to the compounds represented by formula (Z-28), 7. The material for a perovskite solar cell according to any one of claims 1 to 6, wherein Y 21 and Y 22 Each independently includes an aryl derivative; optionally, Y 21 and Y 22 Each independently comprises the structural formula represented by formula (B), In formula (B), Q1 and Q2 each independently include At least one of; Q3 includes at least one of a hydrogen atom and a halogen atom; alternatively, Q3 includes a hydrogen atom or a halogen atom; Further optionally, Y 21 and Y 22 Each independently comprises at least one of the structural formulas represented by formula (B-1) to formula (B-9), 8. The material for a perovskite solar cell according to any one of claims 1 to 7, wherein R 21 and R 22 Each independently includes an alkyl-substituted thiophene group, wherein the alkyl-substituted thiophene group includes the structural formula shown in formula (E), R 23 including substituted or unsubstituted C6 to C16 straight chain alkyl groups; Further optionally, R 21 and R 22 The same groups are included.

9. The material for a perovskite solar cell according to any one of claims 1 to 8, wherein The perovskite solar cell material comprises at least one of the compounds represented by formula (X-11) to the compounds represented by formula (X-17), 10. The material for a perovskite solar cell according to any one of claims 1 to 9, wherein R 21 and R 22 Each independently includes an alkyl-substituted aryl group, wherein the alkyl-substituted aryl group includes the structural formula shown in formula (F), R 24 including substituted or unsubstituted C6 to C16 straight chain alkyl groups; Optionally, the alkyl-substituted aryl group includes the structural formula shown in formula (F-1), Further optionally, R 21 and R 22 The same groups are included.

11. The perovskite solar cell material according to any one of claims 1 to 10, comprising at least one of the compounds represented by formula (X-21) to the compounds represented by formula (X-28), 12. A perovskite solar cell comprising: A perovskite absorption layer, comprising two sides opposite to each other along a thickness direction thereof; A hole transport layer, disposed on one side of the perovskite absorption layer; as well as An electron transport layer is arranged on a side of the perovskite absorption layer away from the hole transport layer, and the electron transport layer comprises the material for a perovskite solar cell according to any one of claims 1 to 11.

13. A perovskite solar cell, comprising: A perovskite absorption layer, comprising two sides opposite to each other along a thickness direction thereof; A hole transport layer, disposed on one side of the perovskite absorption layer; as well as The electron transport layer is disposed on a side of the perovskite absorption layer away from the hole transport layer. A passivation layer is disposed between the perovskite absorption layer and the electron transport layer, wherein the passivation layer comprises the material for a perovskite solar cell according to any one of claims 1 to 11.

14. An electrical device, characterized in that: Comprising the perovskite solar cell as claimed in claim 12 or 13.